5. SURVEY OF SERUM PROCALCITONIN CONCENTRATIONS AND BLOOD CULTURE RESULTS IN PATIENTS WITH BACTERIA INFECTION AT A THAI NGUYEN HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Introduction: Procalcitonin (PCT) is a valuable biomarker commonly used to diagnose and monitor infectious inflammation. Objective: To investigate serum procalcitonin concentrations in patients with positive blood culture sepsis and to evaluate the association between serum procalcitonin concentrations and isolated bacterial pathogens.Subjects and methods: A cross-sectional study of 278 patients diagnosed with sepsis at Thai Nguyen A Hospital from January to September 2024.Results: The median serum PCT concentration in the positive blood culture group (22.1 ng/ml) was higher than that in the negative blood culture group (8.32 ng/ml) with p
Keywords: Procalcitonin; sepsis